The Effect of AI Mindset on the Pedagogical Competence of Teachers at Muhammadiyah Vocational High Schools in Sorong Regency - Muhamad Irlan Gustiana; Indri Anugrah Ramadhani; Firman (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study investigates the influence of AI mindset on the pedagogical competence of vocational high school teachers at Muhammadiyah Vocational Schools in Sorong Regency. A quantitative research design was applied using a survey approach to examine the relationship between the research variables. Data were obtained through questionnaires administered to 36 teachers who met the predetermined research criteria. The analysis revealed that AI mindset has a positive and statistically significant relationship with teachers’ pedagogical competence. The Pearson correlation analysis generated a correlation coefficient of 0.561 with a significance level of 0.000, indicating a moderate positive association between the two variables. Furthermore, the results of the simple linear regression analysis showed a regression coefficient of 0.616, suggesting that higher levels of AI mindset are associated with improved pedagogical competence among teachers. Additionally, the coefficient of determination (R²) was calculated at 0.315, meaning that 31.5% of the variation in teachers’ pedagogical competence can be explained by AI mindset, while the remaining 68.5% is attributed to other variables not included in this study. These findings emphasize the importance of developing teachers’ AI mindset as a strategic factor in strengthening pedagogical competence, particularly within the context of ongoing digital transformation and the increasing integration of artificial intelligence in educational practices.